Síntese e caracterização de nanopartículas de óxido de ferro e de grafite magnética fluida (GMF) - Souza, Nicolau Silva de (2008)
In this work were studied the physical properties of magnetic nanoparticles, based on iron oxide, and magnetic graphite fluid particles. The work was developed in three steps: 1) synthesis of the magnetic nanoparticles of iron oxides by the sol-gel and co-precipitation methods, 2) synthesis of the magnetic graphite fluid particles, 3) structural, microstructural and magnetic characterization of the samples. The morphological properties of the iron oxide nanoparticles, by the MEV-FEG images, showed that the samples obtained by sol-gel technique have a large tendency to create powder agglomerates. By the way, the samples obtained by coprecipitation showed a mean powder diameter 11nm, calculated from the micrographs images. Although, the same value , obtained from the XRD pattern, and diffraction peaks intensity are ~1.5 nm. From the magnetization curves, zero field cooling (ZFC), field cooling (FC), it was possible to see a phase transition for the locked-state at T ( )K B ≈ 39 ±1 for the sample obtained by sol-gel, and at T ( )K B ≈ 179 ±1 for the sample obtained by co-precipitations. The magnetization values as a function of the applied field showed a superparamagnetic behavior, ensured by the electronic paramagnetic resonance (EPR). The morphological characterization of the magnetic fluid graphite, by the TEM images, also showed an agglomerate state, but it was possible to estimate a mean diameter ~10nm. This unpublished value is much smaller than the observed on the literature. The structural characterization of the magnetic fluid graphite, obtained by infrared spectroscopy, showed that the surfactant particles (CTAB) still present on the magnetic fluid graphite surface. The surfactant particles are the responsible for the solution stability; From the magnetization measurements, as a function of the field, the graphite particles showed a typical ferromagnetic behavior. The (ZFC) magnetization measurements showed that the graphite particles have a non-null magnetization at room temperature, and the aqueous suspension doesn`t have influence on the magnetization behavior. The obtained results according to the synthesis way agree with the results showed in the literature. For the iron oxide nanoparticles it has been observed the superparamagnetic behavior in all the samples. The structural properties are ruled according to the synthesis process. On the other hand, for the magnetic graphite fluid particles, the magnetization process was made by the oxi-reduction method controlled on the vapor phase, with controlled atmosphere. After the magnetization process, was obtained by the first time the synthesis of the magnetic graphite fluid, initially on water suspension, with the magnetization properties unchanged.